Early lineages of Vespidae (Hymenoptera) in Cretaceous amber. (April 2017) - PERRARD, ADRIEN; GRIMALDI, DAVID; CARPENTER, JAMES M.
Abstract: Three wasp (Hymenoptera: Vespidae) fossils in Cretaceous amber (Late Albian) of northern Myanmar are described. Two are new species of the Mesozoic genus Curiosivespa (Rasnitsyn): C. zigrasi sp.n. and C. striata sp.n. The third species, Protovespa haxairei gen.n. et sp.n., has a combination of features unique among Mesozoic Priorvespinae and the extant subfamilies. These well preserved fossils provide new morphological data for a cladistic analysis of the basal lineages of Vespidae. Results suggest that Euparagiinae is the sister group of all other Vespidae. The new genus Protovespa appears more closely related to extant Masarinae, Eumeninae and social wasps than to Priorvespinae. We assign it to a new subfamily: Protovespinae. Finally, fossil information combined with a phylogenetic tree shows that the main groups of Vespidae probably evolved during the Early Cretaceous. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:1E7E4796‐6E70‐4D81‐BB34‐0FEEA765DC25 .